2012
DOI: 10.1016/j.knee.2011.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Change in body mass index during middle age affects risk of total knee arthoplasty due to osteoarthritis: A 19-year prospective study of 1003 women

Abstract: The evidence linking body mass index (BMI) to severe OA shows a strong association in the knee. There are limited data exploring the effect of BMI on the risk of joint arthroplasty in a healthy population with long periods of follow up. We compared the self-reported BMI at age 20, measured BMI at baseline, year 5 and year 10 with the year 19 risk of total knee arthroplasty (TKA) in a well-described, population based cohort of healthy women. A total of 733 women attended the 19th year visit, of whom 31 underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 19 publications
0
21
1
Order By: Relevance
“…28 As well as being overweight or obese, weight gain is associated with the risk of receiving a total knee replacement. 31,32 Few data exist on the association of obesity with knee pain. In a cohort of 594 women, BMI at baseline was associated with self-reported knee pain 14 years later.…”
Section: Epidemiology Of Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…28 As well as being overweight or obese, weight gain is associated with the risk of receiving a total knee replacement. 31,32 Few data exist on the association of obesity with knee pain. In a cohort of 594 women, BMI at baseline was associated with self-reported knee pain 14 years later.…”
Section: Epidemiology Of Obesitymentioning
confidence: 99%
“…31 The results of other studies have shown increased risk of knee OA or total knee replacement in association with weight gain, but these studies were underpowered to detect reduced risk with weight loss. 32,33 The evidence suggests that obesity leads to knee OA and pain, and that weight loss will reduce both clinical OA and knee pain. Weight loss is achievable with the help of various interventions, and although maintenance of reduced weight is difficult, modifiable predictors have been identified (Box 1).…”
Section: Weight Loss and Oamentioning
confidence: 99%
“…It is associated with an increase in medical comorbidities including hypertension, coronary artery disease, diabetes, and degenerative joint disease [7,32]. These patients potentially may be at increased risk for having osteoarthritis develop, and may need TKA at an earlier age [6,26]. However, surgical interventions in these patients may be associated with more technically demanding procedures and higher complication rates [3].…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with those of previous studies. Nicholls et al observed that BMI is the strongest predictor for requiring a TKR in middle-aged patients, and that an increase in the BMI of 1 unit at baseline (median age 59 years) is associated with a 10.5% increased risk of TKR during 19-year followup (1). In a study by Gandhi et al, obese patients who required and underwent joint replacement surgery were 7.9 years younger than the nonobese patients (61).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a modifiable risk factor for knee osteoarthritis (OA) and may contribute to the need for a total knee replacement (TKR) (1)(2)(3). The risk of developing degenerative joint disease increases 36% for every 2-unit (5 kg) increase in body mass index (BMI) (4).…”
Section: Introductionmentioning
confidence: 99%